Teaching Strategies, School Environment, and Culture: Drivers of Creative Pedagogy in Ghanaian Schools - Dickson Adom; Ekta Sharma; Sandeep Sharma; Isaac Kwabena Agyei (Studies in Learning and Teaching, 2021)
Creative pedagogy in educational institutions has been the mainstay of sustainable development globally as it ensures high standard human capital with a high level of imagination and problem-solving potentials. However, there are several drivers of creative pedagogy. This exploratory study employed the embedded mixed methods design with qualitative and quantitative approaches aimed at exploring the perspectives of teachers in selected pre-tertiary institutions in Ghana on the teaching strategies, school environment, and culture as drivers of creative pedagogy, using Lin’s creative pedagogy theory. The findings have shown that teaching strategies, school environment, and culture that promotes flexible and independent thinking, problem-solving and collaborative skills ensure students’ creativity development. The study recommends the implementation of learner-centered teaching strategies, a flexible teaching curriculum that encourages creativity development, smaller class sizes, semi-circular seating arrangements, and an introduction of a permissive culture that allows students to think and explore outside the box in Ghanaian schools.